Explore the Application Value of Prospective Monitoring Model in the Nursing Management of Breast Cancer Patients During Perioperative Period - Zhang, Huan; Duan, Yu; Zhou, Fengming (Frontiers in Surgery, 2022)
Purpose: To explore the application value of prospective monitoring model in the nursing management of breast cancer patients during perioperative period. Methods: 300 perioperative breast cancer patients admitted to our hospital from January to August 2021 were randomly divided into the control group (n=150) and the model group (n=150). Both groups used routine nursing management, and the model group added nursing management based on a prospective monitoring model. The quality of surgical nursing, circumference of the upper limbs, and the scores of disability of arm-shoulder-hand (DASH), exerciseofself-care agencyscale (ESCA), multidimensional fatigue symptom inventory-short form (MFSI-SF) and functional assessment of cancer therapy-breast cancer (FACT-B) were compared of the two groups. Results: Postoperatively, the quality of surgical nursing was better in the model group than in the control group (P<0.05). At 3 months postoperatively, the number of cases of upper limb lymphedema was higher in both groups than before (P<0.05), but there was no statistical difference between the two groups in the preoperative and 3 months postoperative comparisons (P>0.05). At 3 months postoperatively, the total DASH score was higher than preoperatively in both groups, but lower in the model group than in the control group (P<0.05). After nursing, the ESCA and SSES scores of each dimension were higher in both groups than before, and the model group was higher than the control group (P<0.05). At 3 months postoperatively, the total MFSI-SF score was lower than preoperatively in both groups, and lower in the model group than in the control group (P<0.05). At 3 months postoperatively, the FACT-B scores of each dimensions were higher in the model group than in the control group (P<0.05). Conclusion: The implementation of nursing management based on a prospective monitoring model for breast cancer patients during the perioperative period has important clinical value in improving the quality of surgical nursing and improving postoperative upper limb lymphedema, upper limb function, self-care ability, social self-esteem, cancer-related fatigue symptoms, quality of life, etc.